Faune malacologique de la plate-forme Ttunisienne: étude de quelques dragages et carottages effectués à l’intérieur ou au large du golfe de Gabes - ROSSO, Jean-Claude (INSTM Bulletin : Marine and Freshwater Sciences, 1978)
Analysis of the malacological fauna from a set of 25 samples (8 dredging and 17 cores) gives information concerning past and recent associations and the evolution of biotopes during the last millenia. The past extent of the sea grasses and their disappearing as a consequence of deepening and silting up, are the main events suggested by this qualitative analysis.